2009
DOI: 10.1016/j.virol.2008.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of p53 by mitogen-activated protein kinase pathways and protein kinase C δ during avian reovirus S1133-induced apoptosis

Abstract: ARV S1133 infection caused apoptosis in vivo and in vitro; however, the intracellular signaling pathways have not been fully delineated. We have previously demonstrated that ARV S1133 activates proapoptotic signaling from Src to p53, and further investigated how ARV S1133 modulates p53. We found that ARV S1133 forms syncytia and induces apoptosis in CEF, DF1 and Vero cells with different kinetics. Enhancement of p53 phosphorylation and DNA-binding capacity to bax and bad promoters was found in this study to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 67 publications
3
41
0
Order By: Relevance
“…6C, p-p38 MAPK was not suppressed by PP2 inhibitor or overexpression of Csk, suggesting that Src is not the upstream inducer of p38 MAPK. These data are in agreement with our earlier report (33). It is also interesting to note that the expression level of p38 MAPK and Src in caveolin-1 or dynamin-2 siRNA-treated cell lysates was not significantly altered (Fig.…”
Section: Inhibition Of Ras P38 Mapk and Src Suppressed Arv-induced supporting
confidence: 93%
See 3 more Smart Citations
“…6C, p-p38 MAPK was not suppressed by PP2 inhibitor or overexpression of Csk, suggesting that Src is not the upstream inducer of p38 MAPK. These data are in agreement with our earlier report (33). It is also interesting to note that the expression level of p38 MAPK and Src in caveolin-1 or dynamin-2 siRNA-treated cell lysates was not significantly altered (Fig.…”
Section: Inhibition Of Ras P38 Mapk and Src Suppressed Arv-induced supporting
confidence: 93%
“…It was an extension of earlier studies by our laboratory in which it was discovered that p38 MAPK and Src signaling pathways triggered by ARV that are beneficial for ARV replication and apoptosis induction (31,33). In this study, the use of a panel of chemical inhibitors, DN mutants together with siRNAs targeting caveolin-1 and dynamin-2 to characterize ARV entry into host cells revealed that ARV uses a cholesterol and caveolin-1-mediated and dynamin-2-dependent endocytosis that requires activation of Ras, p38 MAPK, and Src signaling pathways.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Enrichment of the MAPK pathway within the PBLs at 1 DPI is hypothesized to cause the downstream changes in cytokine-cytokine receptor and p53 signaling seen in the spleen at 5 DPI. MAPK and p53 pathways are associated with apoptosis, tumor suppression, and viral infection (15,29). The increase in apoptotic activity in the birds with severe pathology may contribute to the observed pathology.…”
Section: Discussionmentioning
confidence: 99%